The impact of deafness; theory of mind and child development - Sibanda, Patrick (Pure and Applied Science Advances, 2017)
This paper adopts a wider conception of language which goes beyond viewing language as being limited to speech. The concept of language in this paper includes all forms of socially agreed systems of exchanging and communicating ideas and information which include sign language as a formal language of interaction for the deaf. Thus the paper is premised on the cultural model of deafness which designates sign language as the primary medium of communication for the deaf while at the same time the paper is cognizant of the impact of deafness on child development with regards to aural-oral environments. In these regards, the paper links the impact of deafness to the concept of theory of mind development in order to seduce parents, educators and other stakeholders to strongly consider the need for deaf children to be fully exposed to sign language and deaf culture as a way of promoting their overall development. The paper concludes that; while deafness does impact on child development, quality exposure to and fluency in sign language can facilitate theory of mind development hence mitigate the impact. In the same vein, the impact of deafness becomes an even more critical phenomenon with regards to theory of mind development discourses.